1998
DOI: 10.1046/j.1365-2141.1998.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma thrombopoietin (TPO) levels and expression of TPO receptor on platelets in patients with myelodysplastic syndromes

Abstract: Summary. Data on endogenous thrombopoietin (TPO) levels and their regulation in myelodysplastic syndromes (MDS) are sparse. We examined the plasma TPO level of 85 MDS patients by a sensitive enzyme immunoassay and the platelet expression of TPO receptor (TPO-R) protein, which metabolizes endogenous TPO, in 19 MDS patients with an equilibrium binding assay using 125 I-TPO. The MDS patients had higher plasma TPO levels (7·0 Ϯ 9·3 fmol/ml) than 52 normal subjects (P < 0·0001). Refractory anaemia (RA) patients (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
2
19
2
1
Order By: Relevance
“…28 Increased production and destruction of platelets may accelerate TPO consumption in patients with RAEB, leading to a decrease in plasma TPO levels. Although one report demonstrated increased TPO receptors on the megakaryocytes of MDS patients using flow cytometry, 14 we were unable to reproduce their results (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…28 Increased production and destruction of platelets may accelerate TPO consumption in patients with RAEB, leading to a decrease in plasma TPO levels. Although one report demonstrated increased TPO receptors on the megakaryocytes of MDS patients using flow cytometry, 14 we were unable to reproduce their results (data not shown).…”
Section: Discussioncontrasting
confidence: 50%
“…13,14 While patients with RAEB had consistently low TPO levels, patients with low-risk MDS (RCUD, RCMD, and MDS-U) produced highly variable results. Feng et al recently demonstrated similar variability among patients with hypoplastic MDS and reported the usefulness of TPO in distinguishing hypoplastic MDS from AA; 21 however, the significance of high TPO levels in a subset of patients with low-risk MDS was not the focus of the authors' attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 To date, measurements of soluble circulating mediating factors in marrow failure have been limited largely to one or two cytokines in AA [5][6][7][8][9] and MDS. 10,11 Because of the complex array of proteins involved in an immune response, the measurement of a single cytokine is likely insufficient to assess alterations in disease. We conducted a comprehensive analysis of 31 cytokines, chemokines, and growth factors in the plasma of healthy volunteers, AA, and MDS patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, studies on TPO levels in MDS showed significantly high levels in RA patients and generally low levels in RAEB and RAEB-t patients. 15,30,31 It was also reported that a significant inverse relationship between the TPO concentration and platelet count exists in RA patients, but not in RAEB or RAEB-t patients. However, in this study, both RAEB and CMML patients showed high TPO levels when their CFU-meg were reduced, suggesting no difference among subtypes.…”
Section: Discussionmentioning
confidence: 99%